Analisis Kadar Vitamin C, Kalsium dan Posforus pada Cabai Rawit (Capsicum frustescens L.) Hasil Pengawetan - Nurjannah, Ida; Sabang, Sri Mulyani; Afadil, Afadil (Universitas Tadulako, 2018)
This study aimed to determine the levels of vitamin C, calcium and phosphorus of the preserved chili pepper. In this research, two preservation techniques were applied, cooling and drying. For analysis of vitamin C was used the iodometric method, the results obtained in the technique of cooling was 11.08 mg/100 g and the drying technique was 9.85 mg/100g. For calcium and phosphorus analysis was analyzed by using the spectrodirect instrument, research result obtained for calcium in the cooling technique was 20.00 mg/L and the drying technique was 12.33 mg/L while for phosphorus of the cooling technique was 27.66 mg/L and the drying technique was 55.16 mg/L.